The process and performance comparison of polyamide 12 manufactured by multi jet fusion and selective laser sintering. (November 2019) - Xu, Zhiyao; Wang, Yue; Wu, Dingdi; Ananth, K. Prem; Bai, Jiaming
Abstract: This study is dedicated to comparing the processes of selective laser sintering (SLS) and multi jet fusion (MJF), and evaluates the morphologies, thermal and mechanical properties of the polyamide 12 (PA12) parts fabricated by these two technologies. The results showed that the PA12 powders used by these two technologies both had approximately elliptical shapes, similar particle sizes, distributions and sintering windows. For the printed parts, the surface roughness of the MJF where detailing agent was applied on was significantly better than the roughness of SLS parts. During the processing, with the powerful instant heating capability of laser, the degree of particle melting in SLS was higher than that of MJF. The mechanical properties of the MJF parts was relatively lower than that of SLS, which could be explained by the lower density of the MJF parts. However, the printing speed of MJF was almost 10 times than that of SLS's by the reason of different processing principles.